2023
DOI: 10.3390/v15061262
|View full text |Cite
|
Sign up to set email alerts
|

Ketogenic Diet and Ketone Bodies as Clinical Support for the Treatment of SARS-CoV-2—Review of the Evidence

Abstract: One of the proposed nutritional therapies to support drug therapy in COVID-19 is the use of a ketogenic diet (KD) or ketone bodies. In this review, we summarized the evidence from tissue, animal, and human models and looked at the mechanisms of action of KD/ketone bodies against COVID-19. KD/ketone bodies were shown to be effective at the stage of virus entry into the host cell. The use of β-hydroxybutyrate (BHB), by preventing the metabolic reprogramming associated with COVID-19 infection and improving mitoch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 216 publications
0
4
0
Order By: Relevance
“…Several studies in the literature demonstrated that the supplements used in this study like dopamine, glucosamine, D -xylose, cysteine, ( R )-3-hydroxybutanoate, lovastatin, and simvastatin have the potential to develop therapeutic strategies to fight SARS-CoV-2. Dopamine is an important neurotransmitter and required for proper functioning of the body including movement, memory, and motivation. Administration of dopamine reduced the viral replication in CaLu-3 human lung epithelial cells and virus-based cytopathic effect in Vero E6 epithelial cells infected with SARS-CoV-2. , Glucosamine is a common dietary supplement that promotes joint health.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Several studies in the literature demonstrated that the supplements used in this study like dopamine, glucosamine, D -xylose, cysteine, ( R )-3-hydroxybutanoate, lovastatin, and simvastatin have the potential to develop therapeutic strategies to fight SARS-CoV-2. Dopamine is an important neurotransmitter and required for proper functioning of the body including movement, memory, and motivation. Administration of dopamine reduced the viral replication in CaLu-3 human lung epithelial cells and virus-based cytopathic effect in Vero E6 epithelial cells infected with SARS-CoV-2. , Glucosamine is a common dietary supplement that promotes joint health.…”
Section: Resultsmentioning
confidence: 98%
“…N -acetylcysteine was proposed as both in potential treatment and prevention against SARS-CoV-2 in different studies. ( R )-3-hydroxybutanoate is a ketone body that provides an alternative carbon source for the cellular metabolism. Ketogenic diet is recommended as nutritional therapy for the treatment of COVID-19 by restoring perturbed energy metabolism and redox state. Lovastatin and simvastatin are lipid-lowering medications and belong to the statin class exhibiting anti-inflammatory, antithrombotic, and immunomodulatory features . Lovastatin administration in COVID-19 patients led to a significant decrease in the duration of hospitalization in intensive care unit .…”
Section: Resultsmentioning
confidence: 99%
“…These compounds are believed to have the potential to counteract inflammation and provide antioxidant effects within the body [ 58 ]. This, in turn, could potentially reduce the occurrence of age-related diseases and viral infections like COVID-19 [ 59 , 60 ]. However, the exact molecular mechanisms responsible for how ketone bodies alleviate oxidative stress and inflammation remain a topic of ongoing investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical trials using dietary modification, probiotics, prebiotics, and fecal microbiota transplantation are underway to determine their effectiveness in the treatment of acute COVID-19 and possibly enhance the effectiveness of SARS-CoV-2 vaccines [152][153][154][155][156][157][158]. Only long-term clinical data and future research shall provide better insight into the complex bidirectional interaction between the virus and the alimentary tract in healthy patients and those with preexisting gastrointestinal diseases.…”
Section: Discussionmentioning
confidence: 99%